Analysis of Directive Speech Acts in The Film Uang Panai by Asril Sani and Halim Gani Safia - Moh Afandi; Suparni Suparni (Yayasan Kyadiren, 2025)
This study aims to describe the forms and functions of directive speech acts in the film Uang Panai and their relevance to the communicative context between characters. A descriptive qualitative method was employed in this research. The data, consisting of utterances, were collected through observation and note-taking techniques and analyzed using the theoretical framework of directive speech acts. The results reveal six categories of directive speech acts: (1) requests (14 data); (2) advice (10 data); (3) commands (9 data); (4) invitations (6 data); (5) prohibitions (4 data); and (6) criticisms (2 data). The dominance of request speech acts reflects a preference for persuasive and non-coercive communication strategies within the characters' interactions. These findings demonstrate that directive speech acts serve not only as a narrative driver for the plot but also as a representation of the cultural communication of the Bugis-Makassar community, which are deeply rooted in social values and politeness.